Motor phenotypic alterations in TgDyrk1a transgenic mice implicate DYRK1A in Down syndrome motor dysfunction - Martı́nez de Lagrán, M; Altafaj, X; Gallego, X; Martı́, E; Estivill, X; Sahún, I; Fillat, C; Dierssen, M (Neurobiology of disease, 2004)
Motor deficits are among the most frequent impairments in Down syndrome (DS), but their neuropathological and molecular bases remain elusive. Here we investigate the motor profile of transgenic mice overexpressing Dyrk1a, Tg(Dyrk1a)1Cff (hereafter TgDyrk1a), a candidate gene hypothesized to cause some of the neurological defects associated with DS. We have previously shown DYRK1A expression in the cerebellum and functionally related structures, most brainstem motor nuclei and spinal cord, supporting a role for Dyrk1a in controlling motor function. Here we demonstrate that TgDyrk1a mice present DYRK1A overexpression in these areas along with specific motor dysfunction. The main finding that emerged was impairment of motor learning and alteration of the organization of locomotor behavior, which agrees with reported clinical observations in subjects with DS. These results confirm and extend previous data and provide further insight to the functional domains that might be altered in TgDyrk1a mice and underlying molecular mechanisms of DS motor dysfunction.